The Outside In: The intensification of landscape in the Anthropocene - McIntosh, Jacqueline; Marques, Bruno; Palmer, Madeleine; Ujung, Verarisa (Enquiry The ARCC Journal for Architectural Research, 2019)
Degradation of ecosystem services, scarcity of resources and the erosion of the planet’s capability to absorb waste is of immediate concern. This situation is novel in its speed, its global and local scale and its threat to the planet and its people. Inspired by the recent discourse of the Anthropocene, this paper explores the convergence of human and nature as they confront generative and destructive forces in two distinctly different settings. Using a case-study approach, this paper adopts the cyborg landscape as a conceptual framework to address the interconnectedness of systems, and scale and poetic brief to accommodate the environment while supporting the needs of our contemporary society. By using nature’s generative capacities as well as its destructive tendencies and by blurring the disciplinary boundaries between interior architecture and landscape architecture, this paper considers two different locations in New Zealand: a post-industrial site on Auckland’s urban waterfront and a remote active volcanic site located on White Island. It finds opportunity to examine intensified inhabitation through acts of immersion and extraction in the "new normal” where nature’s interrelated systems and the artifice of the Anthropocene create innovative and dynamic possibilities. It concludes that the creation of a link between natural processes and responsive technologies can provide solutions to address the complexity of climate change.